Critical thinking disposition among students of a public university in Lima Metropolitan Area - Delgado Vásquez, Ana Esther (2019)
Critical thinking disposition was researched in male and female students from different professional areas of a public university in Lima Metropolitan Area. One thousand three hundred seventy-six (1,376) university students were recruited using a non-probability quota sampling. Comparisons were made considering the participants’ different professional areas and sex. The results show that there are only significant statistical differences in the Curiosity dimension of the test according to the professional areas of the university.